The Bible and Gender Troubles: American Evangelicals Debate Scripture and Submission - Padgett, Alan G. (Dialog, 2008)
This article surveys the recent debates about gender roles and submissions in American evangelical theology since the 1960's. It argues that the so-called “complementarian” viewpoint, in which women are equal in being but submissive to men in gender roles, is not the same as the traditional Christian patriarchal viewpoint. Both biblical equality and complementarian views are thus revisionist. This article introduces the “return to the Trinity” in this debate as one of the more interesting moves in recent years, and suggests some lessons for mainline Protestants.